2020
DOI: 10.3390/ijerph17051703
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Factors Affecting the Timing of Menarche: The Potential for Climate Change to Impact Women’s Health

Abstract: Menarche is the first occurrence of a woman’s menstruation, an event that symbolizes reproductive capacity and the transition from childhood into womanhood. The global average age for menarche is 12 years and this has been declining in recent years. Many factors that affect the timing menarche in girls could be affected by climate change. A systematic literature review was performed regarding the timing of menarche and four publication databases were interrogated: EMBASE, SCOPUS, PubMed, and Cochrane Reviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 185 publications
(231 reference statements)
4
42
1
2
Order By: Relevance
“…Based on the study outcomes, future interventions would consider targeting elementary-school girls through the school health system. Developing interventions that target elementary-school girls is logical because menstrual pain tends to occur after menarche [ 6 ], the age at menarche is becoming lower [ 36 , 37 ], eating habits are becoming more convenience-oriented, and elementary-school girls are at a stage where they form habits in their daily life [ 38 ]. Therefore, it is critical for girls to form healthy dietary habits to protect themselves from exposure to EDCs starting at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study outcomes, future interventions would consider targeting elementary-school girls through the school health system. Developing interventions that target elementary-school girls is logical because menstrual pain tends to occur after menarche [ 6 ], the age at menarche is becoming lower [ 36 , 37 ], eating habits are becoming more convenience-oriented, and elementary-school girls are at a stage where they form habits in their daily life [ 38 ]. Therefore, it is critical for girls to form healthy dietary habits to protect themselves from exposure to EDCs starting at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, menarcheal age is 13 years [6]. Carnelo et al, in a systematic review, reported age at menarche in a USA population to be 12 years [7]. In Nigeria, the average age at menarche varies from one geopolitical zone to another [8]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results based on such a small group of patients did not reveal any significant gynecological dysfunction. The median age of menarche seems to be higher than current global average which is 12 years, but we need to notice that this age is declining in recent years [23].…”
Section: Discussionmentioning
confidence: 81%